How to promote the pragmatic awareness and avoid the fossilization phenomenon through a role play activity in English as a foreign language classes - Oliveira, Patrícia Flasmo de (BELT - Brazilian English Language Teaching Journal, 2021)
Many people, even after spending a lifetime studying a foreign language are prone to get stuck in a certain grammatical domain no matter the efforts made and the amount of the target language input offered in the classroom. Unfortunately, the great majority who pursuits their dreams to be the closest possible to a native like speaker, the lack of ability to analyze and synthesize linguistic elements makes them persist in the same errors, establishing a phenomenon known as Fossilization in their learning process. In fact, Fossilization can occur in all learning process levels: phonological, grammatical, lexical and pragmatic and the errors made seem to be similar from individual to individual. In an attempt to avoid this Fossilization process concerning the pragmatically ability to communicate, this article aims to present a suggestion of a role-play activity involving strategies to enhance pragmatic awareness related to politeness theory.